RESTRAINED SQUARE FREE DETOUR NUMBER OF A GRAPH (International Journal of Food and Nutritional Sciences, 2022)
In this paper, we define and determine the results on restrained square free detour number ofsome standard graphs and special graphs. Furthermore, we discuss relationship between thedetour number and restrained square free detour number.The bounds of the restrained squarefree detour set of a graph are also established.